2004
DOI: 10.1038/sj.sc.3101593
|View full text |Cite
|
Sign up to set email alerts
|

Electromotive drug administration of lidocaine to anesthetize the bladder before botulinum-A toxin injections into the detrusor

Abstract: Study design:Prospective, open label, cross-over-designed clinical study. Objective: To evaluate the effectiveness of an instillation of lidocaine into the bladder with versus without electromotive drug administration (EMDA) to anesthetize the bladder before botulinum-A toxin injections. Setting: Neurourology, Swiss Paraplegic Center, Balgrist University Hospital, Zurich, Switzerland. Methods: In all, 28 patients with severe neurogenic detrusor overactivity but preserved bladder sensibility were treated with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…Local anaesthesia using electromotive drug administration of 2% lidocain was applied in patient 2 because of preserved bladder sensibility due to an incomplete spinal cord lesion (table 1) [21].…”
mentioning
confidence: 99%
“…Local anaesthesia using electromotive drug administration of 2% lidocain was applied in patient 2 because of preserved bladder sensibility due to an incomplete spinal cord lesion (table 1) [21].…”
mentioning
confidence: 99%
“…Botulinum toxin application into the istration on pain scores during subsequent botulinum toxin injections indicated that electromotive lidocaine administration was associated with a significant decrease in the pain score and ensured painless application of botulinum toxin in patients with preserved sensation. 33 This concept of electromotive drug administration was later applied to botulinum toxin to evaluate whether electromotively driven botulinum toxin application was effective in rabbits. 34 Compared with injections, electromotive lidocaine administration resulted in more uniform and homogeneous botulinum spread throughout the urothelium on immunohistologic staining.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that, compared to spinal or general anaesthesia, the local anaesthesia induced by lidocaine with EMDA saves around 15% of the costs [47]. This treatment modality allows clinicians to perform bladder distention also in an office setting, with equivalent results to distention under general anaesthesia and potentially less morbidity and lower costs [53,54].…”
Section: Costsmentioning
confidence: 99%
“…Intravesical electromotive administration of both 5 and 15 mg oxybutynin significantly increased cystometric bladder capacity and significantly reduced the first volume for the onset of uninhibited detrusor contractions, and duration and maximum pressure of these contractions, in patients with neurogenic detrusor overactivity [29,30]. Clinical reports demonstrated that intravesical EMDA of local anaesthetics produced sufficient anaesthesia to allow transurethral resection of bladder tumours [45,46], to perform botulinum toxin A injections into the detrusor muscle [47], to administer intravesical capsaicin [48], and to determine cystodistention in the treatment of refractory interstitial cystitis and chronic noninfectious cystitis [49][50][51].…”
Section: Recent Developments In Physical Approachesmentioning
confidence: 99%